The Four Horsemen of the Apocalypse - Minnelli, Vicente (Warner Home Video, 2003)
Political conflict drives a wedge between the related Von Hartrotts and Desnoyers families causing the death of their patriarch Julio Madariaga. During the occupation of Paris, Karl Von Hartrott and his son are in the Nazi high command. Julio Desnoyers lives the high life and his sister Chi-Chi joins the Resistance. Only after Julio had an affair that raises his moral consciousness does he learn the true nature of the war, and joins the fight against the Nazis.